Identification and characterization of endophytic fungi associated with the leaves of Moringa oleifera Lam - Panes, Vivian A (Archīum Ateneo, 2017)
Fungal endophytes live within host plants and are recently gaining interest as sources of biologically active secondary metabolites. In this research, fungal endophytes associated with leaves of Moringa oleifera Lam. were isolated, characterized and identified. Leaf samples from two moringa trees were collected from Barangay Pandan, which is an urban area and Barangay Sapang Bato considered as a rural area with the highest elevation of all the barangays of Angeles City. All leaf samples were rid of debris by rinsing with tap water. A flame-sterilized one-hole puncher was used to bore 54 explants from leaves collected from each tree of each site (6 mm diameter). Explants were surface-sterilized by washing them with distilled water followed by 70% ethanol for 20 s, and then 0.52% NaOCl solution (commercially available bleach) for 30 s before finally rinsing them with sterile distilled water. The surface sterilized explants were then transferred to plates containing malt extract agar (MEA) amended with streptomycin (250 mg L-1) to prevent bacterial growth. The isolated fungal endophytes were characterized and identified based on their morphocultural characters. Results showed that a total of 24 fungal morphospecies were isolated. These were identified as belonging to the genera Fusarium, Xylaria, Pestalotiopsis, Aspergillus, Nigrospora, Stachybotrys, Rhizoctonia, and Macrophomina. Majority of the fungal endophytes isolated failed to produce spores and therefore were considered to be Mycelia sterilia. Fourteen fungal endophytes were extracted from Barangay Pandan as compared to 10 from barangay Sapang Bato. Of the nine different taxa identified in the two sites, Mycelia sterilia, Pestalotiopsis sp. and Rhizoctonia sp. were found to be common fungal endophytes extracted in both sites.